2021
DOI: 10.1371/journal.pone.0248652
|View full text |Cite
|
Sign up to set email alerts
|

The association of COVID-19 occurrence and severity with the use of angiotensin converting enzyme inhibitors or angiotensin-II receptor blockers in patients with hypertension

Abstract: Background A number of studies have reported the association between the use of angiotensin-converting enzyme inhibitor (ACEI) and angiotensin-II receptor blocker (ARB) medications and the occurrence or severity of coronavirus disease 2019 (COVID-19). Published results are inconclusive, possibly due to differences in participant comorbidities and sociodemographic backgrounds. Since ACEI and ARB are frequently used anti-hypertension medications, we aim to determine whether the use of ACEI and ARB is associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
2
13
1
2
Order By: Relevance
“…One hypothesis postulates that ACE inhibitors and/or ARBs, taken by approximately 65% of our participants with hypertension, may mediate changes in baseline inflammation or in ACE2 receptor expression or affinity through the renin-angiotensin-aldosterone system [ 70 ]. Large meta-analyses and observational studies have not confirmed this hypothesis [ 70 – 72 ], but if ACE2 or related receptors are down-regulated and viral replication is thus initially limited, lower nAb responses may reflect less early antigen stimulation. We saw no statistically significant difference in nAb responses between hypertensive individuals who did or did not report ARB or ACE inhibitor use, but few participants were not on these medications and the directionality of the nonsignificant differences we observed—lower odds of a nAb response and lower titers among those on ARBs or ACE inhibitors—are consistent with this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis postulates that ACE inhibitors and/or ARBs, taken by approximately 65% of our participants with hypertension, may mediate changes in baseline inflammation or in ACE2 receptor expression or affinity through the renin-angiotensin-aldosterone system [ 70 ]. Large meta-analyses and observational studies have not confirmed this hypothesis [ 70 – 72 ], but if ACE2 or related receptors are down-regulated and viral replication is thus initially limited, lower nAb responses may reflect less early antigen stimulation. We saw no statistically significant difference in nAb responses between hypertensive individuals who did or did not report ARB or ACE inhibitor use, but few participants were not on these medications and the directionality of the nonsignificant differences we observed—lower odds of a nAb response and lower titers among those on ARBs or ACE inhibitors—are consistent with this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the use of ACEI was significantly associated with a higher risk of hospitalization and mechanical ventilation compared to non-users or ARB users. The study of Li et al [23] showed that neither ACEI nor ARB use was associated with increased mortality or other adverse events for the COVIDtreated patients than ACEI/ARB-non-users [23]. However, such an extensive study has some limitations: the majority of the patients (around 93%) were male; the study did not consider the use of diuretics in the previous treatment of the patients and other sources of bias/confounder factors.…”
Section: Findings From the Reported Studies On The Raas Inhibitors Effects In Covid-19 Patientsmentioning
confidence: 99%
“…Such categories are older, hypertensive, male patients, diabetes, chronic kidney, and cardiovascular disease. The same categories of patients are also known to receive more frequent medication, including ACEI/ARBs [18,19,22,23]. Therefore, understanding the exact effects and mechanism of action of RAAS inhibitors becomes a matter of particular importance.…”
Section: Controversies Regarding the Raas Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hampir dua pertiga orang di atas 60 tahun memiliki tekanan darah tinggi (WebMD, 2021). Kemungkinan penyebab lainnya ialah akibat penggunaan obat antihipertensi golongan ACE inhibitor dan angiotensin receptor blocker (ARB), yang dapat meningkatkan kadar Shirly Gunawan, enzim yang disebut angiotensin converting enzyme 2 (ACE2) di dalam tubuh (Li et al, 2021)…”
Section: Hasil Dan Pembahasanunclassified